مركزية الخطابي رحمه الله (ت:388ه) في الدرس الصوتي القرآني - حذيق, العيد (My University, 2023)
هذه المداخلة بعنوان: مركزية الخطابي رحمه الله (ت:388ه) في الدرس الصوتي القرآني؛ وهي دراسةٌ في جهود الخطابي رحمه الله التأسيسية في الإعجاز الصوتي التأثيري في القرآن الكريم، وبيان أثر هذه الجهود فيمن جاء بعده. ولمعالجة هذا الإشكال؛ فإني قسَّمتُ المداخلة إلى مقدمةٍ ومقصدين وخاتمة. أما المقدمة فقد مهدت فيها بالتعريف بالإعجاز الصوتي، والتعريج على أبرز رواد الدرس الصوتي في التراث العربي. وأما المقصد الأول؛ فقد عنونته بـ: الخطابي رائد الإعجاز الصوتي التأثيري، وجعلته في أوليَّة الخطابي رحمه الله التاريخية في طرق باب الدرس الصوتي للقرآن الكريم، وما له من أثرٍ على المتلقين، وذلك من خلال ما ختم به كتابه (بيان إعجاز القرآن). وأما المقصد الثاني؛ أثر جهود الخطابي في المهتمين بالدراسات الصوتية القرآنية؛ فقد كان رصدًا لتأثر من جاء بعد الخطابي بطرحه، واستثمارهم فيما كتب لاستنطاق مكامن الدرس الصوتي، لا سيما المحدثين، كما فعل الرافعي ودراز رحمها الله. وقد توصلت في الخاتمة إلى نتائج أهمها: - الخطابي رحمه الله من الشخصيات الجديرة بالدراسة في قضية الإعجاز الصوتي التأثيري؛ كونه من الرواد الذين أدرجوا الدرس الصوتي في المجال القرآني، ثم إنه جمع بين وصف الظاهرة وبيان الأثر، ولم يقتصر على أحدهما دون الآخر. - تأثير القرآن الكريم حاصل في كافر الناس ومؤمنهم، وإنسهم وجنهم، بل وحتى في الجمادات، وقد دلل الخطابي رحمه الله على كل جزئية مما ذُكر من القرآن الكريم نفسه. Abstract This article entitled " The Centrality of Al-Khattabi in the Quran's Phonetic Lesson" is a study of the founding efforts of Al-Khattabi’- may God have mercy on him(died: 338 h)- in the influential phonetic inimitability in the Holy Qur’an, and the impact those efforts made on who came after him. To address this subject, I divided the article into an introduction, two chapters and a conclusion. The introduction paves the way defining the phonetic inimitability, and reviewing the most prominent pioneers of the phonetic lesson in the Arab heritage. The first chapter titled "Al-Khattabi, the Pioneer of the Influential Phonetic Inimitability" deals with Al-Khattabi's historical precedence in tackling the phonetic lesson of the Holy Qur’an, and its impact on the recipients, through what he concluded his book (Explanation of the Miracle of the Qur’an) with. The second chapter " The impact of Al-Khattabi's Efforts on Those Interested in Quranic Phonetic Studies" investigates the influence of Al-Khattabi's proposal on those who came after him, and their investment in what was written to examine the sources of the phonetic lesson, especially the modern scholars, as Al-Rafi’i and Diraz, may God have mercy on her, did. In the conclusion, I summarized the most important results: Al-Khattabi, may God have mercy on him, is one of the figures worthy of study in the subject of the miraculous effect of sound. Being one of the pioneers who included the phonetic lesson in the Qur’anic field, he combined the description of the phenomenon with the statement of its effect, and was not limited to one or the other. - The influence of the Holy Qur’an is present in people who are believers and non-believers, in humans and jinn, and even in inanimate objects. Al-Khattabi, may God have mercy on him, demonstrated every part of what was mentioned from the Holy Qur’an itself.
مداخلة
Keywords: الخطابي، الإعجاز التأثيري، الدرس الصوتي، القدماء، المُحدَثُون; Al-Khattabi, the effectual inimitability, the phonetic lesson, the ancient scholars, the modernists